Midterm Outcome of Kidney Transplantation From Donors With Thin Basement Membrane Nephropathy. Issue 4 (April 2018) - Choi, Chanjoong; Ahn, Sanghyun; Min, Seung-Kee; Ha, Jongwon; Ahn, Curie; Kim, Yonsu; Lee, Hajeong; Min, Sang-il
Abstract : Background: Thin basement membrane nephropathy (TBMN) is the most common cause of persistent glomerular hematuria. Most individuals with TBMN show a benign course, although it can be difficult to distinguish it from early stages of progressive renal diseases. However, only limited studies address the prognosis of donors with TBMN and their recipients. Methods: From 2007 to 2016, 11 recipients received kidney grafts from donors with TBMN, and their clinical data were analyzed retrospectively. Follow-up protocol kidney biopsies were given to the recipients at 10 days and 1 year after transplantation. The donors were also received a follow-up evaluation of their renal function and were interviewed via telephone survey. Results: All donors were living, and their kidney grafts showed TBMN on pretransplantation biopsy. The recipients were followed for 57.4 ± 28.6 months posttransplantation. Seven recipients showed acute rejection by a median of 9.7 months, and all recipients recovered their renal function after treatment. Although 1 kidney failed due to graft arterial occlusion, the functions of the others were preserved during the follow-up period. The donors were followed for 41.0 ± 39.1 months and additionally contacted via telephone survey (in total, 56.8 ± 32.0 months). All the donors maintained their renal function upon clinical follow-up without significant complications and denied any discomfort at the time of the telephone interview. Conclusions: Kidney transplant donors with TBMN and their recipients maintained their renal function through midterm follow-up without significant complications. Therefore, kidney transplantation from donors with TBMN could be a safe option. Abstract : In the largest study of living kidney donors with biopsy-proven thin basement membrane nephropathy (TBMN) with almost 6 years of follow-up, 11 donors had no deterioration in postdonation renal function. Only 2 of 11 recipient grafts showed TBMN, while 9 grafts showed normal glomerular basement membrane on a 10th day posttransplant protocol biopsy.